PERANCANGAN INTERNET OF THINGS (IoT) PADA ALAT PENGERING BIJI CENGKEH BERBASIS ANDROID - Fredin Rimba Saputra; Fauzan Masykur; Angga Prasetyo (KOMPUTEK, 2020)
Currently, clove dryer still uses a manual system that relies on sunlight during the dry season for 4 to 5 days with an average drying time of between 8 and 10 hours per day [1]. The problem with the long drying process of cloves during the rainy season depends on sunlight. Drying cloves that rely on sunlight can only be done during the day at night when cloves can not be dried. The problem is that the increasing clove production is the increasing demand for dry cloves along with the development of the kretek cigarette industry in Indonesia, the production of cloves which requires a dryer that can carry out the drying process without the need to use sunlight so that they can do it anytime without the need for sunlight. The clove dryer uses a NodeMCU ESP8266 microcontroller and is integrated with the android application. The android application is used to control the clove dryer.